Carbon and Nutrient Fluxes in Continental Margins A Global Synthesis - Liu, Kon-Kee.; Liu, Kon-Kee.; Atkinson, Larry.; Atkinson, Larry.; Quiñones, Renato.; Quiñones, Renato.; Talaue-McManus, Liana.; Talaue-McManus, Liana. (Global Change - The IGBP Series, 2010)
This book is a product of the joint JGOFS (Joint Global Ocean Flux Study)/LOICZ (Land–Ocean Interactions in the Coastal Zone) Continental Margins Task Team which was established to facilitate continental margins research in the two projects. It contains signi cant information on the physical, biogeochemical, and ecosystems of continental margins nationally and regionally and provides a very valuable synthesis of this information and the physical, biogeochemical and ecosystem processes which occur on continental margins. The publication of this book is timely as it provides a very strong foundation for the development of the joint IMBER (Integrated Marine Biogeochemistry and Ecosystems Research)/LOICZ Science Plan and Implemen- tion Strategy for biogeochemical and ecosystems research in the continental margins and the impacts of global change on these systems. This initiative will move forward integrated biogeochemical and ecosystems research in the continental margins. We thank all the contributors to this volume and especially Kon-Kee Liu who has dedicated a great deal of time to ensuring a high-quality book is published. IMBER Scienti c Steering Committee Julie Hall LOICZ Scienti c Steering Committee Jozef Pacyna v 1 Preface In general, interfaces between the Earth’s larger material reservoirs (i. e. , the land, atmosphere, ocean, and sediments) are important in the control of the biogeoche- cal dynamics and cycling of the major bio-essential elements, including carbon (C), nitrogen (N), phosphorus (P), sulfur (S), and silicon (Si), found in organic matter and the inorganic skeletons, shells, and tests of benthic and marine organisms.